(3LQGFe ZT GdCOhjI (B: s (3OQGSI ebGQfI (B/ s - (3YeQh Ydi YHOGdefYe Ydis; (3MSfjf YHjOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3jYO GdOhGoA MUGnO oLrgpO GdEfSGf efP HOGjI GdNdjbI(B: (3h bO GeJO h GSJeQ h JWhQ MJi CUHM Ydi nhrUpag h UaGJg GdMGdjI, adG HO Cf ojrfnXnQ Edjg Ydi Cfg VQhQI edMI dG jecf def jMJGLg GdGSJZfGA Yfg(B: (3h jYoqO GdMUhd Ydi GdOhGA GdBef ef Cge Mbhb GdEfSGf(B: (3h UdGMjI GdCOhjI ddGSJNOGe JTJQW GdLhOI(B: (3h GdNdh ef YhGed GdVQQ GdJi bO JDKQ SdkHG Ydi nerf jJOGhi Hg(B. (3h ZnqT GdOhGA ef CNWQ GdLQGFe GdJi oJnYpqQoV UMI GdfGS h CQhGMge ddNWQ GdTOjO(B: (3h jfYcS CKQ GdZT SdkHG HUhQI eHGTQI Ydi bOQI GdTYH Ydi GdYed h GdHfGA(B: (3hjo nbpqhoV GdLghO GdJi JHPdgG GdOhdI ai SHjd caGdI COGA GdNOeGJ GdUMjI(B: (3h jfGd ef SeYI GdLhOI GdJi jJeJY HgG GdOhGA ai GdShb GdYGdei; eeG jdbi HXdGmd SjFI Ydi GdJUOjQ h GdGbJUGO Gdbhei(B. (3SHb JMQje GdTQjYI GdESdGejI ddZT HcGaI UhQI GdbGfhf GdhVYi dg MjK Cf OjffG GdMfja jMGQH ajfG GdeGOjI h GdGfGfjI Hcd eYGfjgG, h jQj ajfG GdSeh h GdHYO Yf GdOfjI(B: (3h GdYOd ai cd TFs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B177-190s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdCOhjIs; (3GdZTs; (3JMQjes; (3GdShb GdYGdejs; (3ZT GdCOhjI s; (3GSJjQGO Ch LdH GdCOhjI GdeZThTIs; (3LQjeI GdMjGRI Ch GdGSJjQGO Ch GdLdHs; (3NOGY GdeJYGbO s; (3LQGFe GdNOGZ heNGdaI GdehGUaGJ s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs